1981
DOI: 10.1021/np50016a002
|View full text |Cite
|
Sign up to set email alerts
|

Histochemistry II. Ginsenosides in Ginseng (Panax ginseng, Root)

Abstract: The location of the ginsenosides, active principle of Panax ginseng root, was determined histochemically. Ginsenosides were found localized outside of the root cambium, particularly in the periderm and outer cortex outside of the phloem. From this result the quality, as affected by the processing method of commercial ginseng, was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0
3

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 7 publications
5
17
0
3
Order By: Relevance
“…The concentrations determined by ELISA agreed well with those determined by HPLC (Kitagawa et al, 1987). ELISA was more sensitive than TLC (Tani et al, 1981) or HPLC (Sticher and Sticher, 1979;Soldati and Sticher, 1980). Moreover, Yamaguchi et al (1988) and Samukawa et al (1995) reported the comparative concentrations of ginsenosides in various commercial ginseng radices analyzed by HPLC.…”
Section: G-rb1 and -Rg1 Concentrations In Panax Spp Measured By Elisasupporting
confidence: 66%
“…The concentrations determined by ELISA agreed well with those determined by HPLC (Kitagawa et al, 1987). ELISA was more sensitive than TLC (Tani et al, 1981) or HPLC (Sticher and Sticher, 1979;Soldati and Sticher, 1980). Moreover, Yamaguchi et al (1988) and Samukawa et al (1995) reported the comparative concentrations of ginsenosides in various commercial ginseng radices analyzed by HPLC.…”
Section: G-rb1 and -Rg1 Concentrations In Panax Spp Measured By Elisasupporting
confidence: 66%
“…인삼의 기능성 지표물질인 ginsenoside의 함량은 연근 (Jang et al, 1983;Lim, 2005), 뿌리의 조직 (Lee et al, 1978;Park et al, 1982;Tani et al, 1981), 뿌리의 부위 (Kim et al, 1984(Kim et al, , 1987, 재배위치 (Li et al, 2009a), 재배품종 (Kwon et al, 1991), 재배지역 (Lee et al, 2004) 등에 따라 상이하다.…”
Section: 서 언unclassified
“…이러한 결과는 ginsenoside 함량이 목질부 (xylem) 및 수 (pith)에는 거의 존재하지 않고, 대부분 주피 (periderm)에 분포 하는데 (Kubo et al, 1980;Tani et al, 1981) …”
Section: 서 언unclassified
See 2 more Smart Citations